Rohingya Muslims in Indonesia: Interaction, Stigmatization and Religious Response - Irwanysah, Irwansyah; Al Asya'ari, Al Asya'ari (FIKRAH, 2022)
Studies on immigrant groups in Indonesia have been increasingly carried out by academics since the arrival of refugees from conflict areas to Indonesia as a transit point to a country that is responsive to immigrants. One of the issues of his study is the Rohingya Muslims. As refugees with Islamic religious identities, their existence is interesting to examine from the perspective of religious communities around the refuge. This study was conducted in the Aceh, Medan, and Makassar regions as the places most visited by Rohingya Muslim groups. This research uses a qualitative approach with case studies. This is intended to be able to map how the response of religious communities to the existence of Rohingya Muslims. The main finding is that the existence of Rohingya Muslims in the three regions has different responses given by various people around them. The cultural basis and religious relations are decisive. In Aceh, strong religious relations resulted in a different response for Rohingya Muslims compared to those in Medan and Makassar, whose backgrounds were more diverse. The location of the comparison is that in Aceh the response based on ukhuwah Islamiyah is more dominant, while in Medan and Makassar the humanitarian response and a firm line of state identity are important signs in responding to the existence of Rohingya Muslims. This response interaction results in acculturation as well as stigmatization